Sex and gender in the Pacific
1 online resource (xix, 211 pages)
Keywords: "This book examines sexuality, gender and health in the Pacific with a focus on three key topics: young people, culture and learning; sexual and reproductive health and well-being; and belonging, connectedness and justice. Sex and Gender in the Pacific is an important read for students, researchers and practitioners working in sexuality and gender studies, public health, public policy, sociology, education, and anthropology"--